Non-Formal Education in Digital Spaces: A Digital Ethnography of Ghanaian Teachers’ Use of WhatsApp Group - Richardson Addai-Mununkum (International Journal of Qualitative Research, 2023)
Research on social media use in education has found evidence of positive outcomes. While the benefits of social media in formal education discourse are known, there is still limited knowledge about its use in non-formal education. This study explored the use of WhatsApp groups in non-formal education. The researcher designed a qualitative virtual ethnographic study based on a community of Ghanaian teachers who utilized WhatsApp to prepare for their promotion examination. The researcher immersed himself as a participant observer in this digital community for 16 months, observing web interface, visuals, text, threaded discussions, and participant interaction. Data generated were analyzed thematically with the aid of Taguette, a qualitative data analysis software. The outcome of the study was an affirmation of limitless possibilities existing in digital spaces to promote non-formal education. Based on this, a recommendation is made for a reexamination of curriculum and pedagogical constructs to forge new directions for teaching and learning.